2005
DOI: 10.1086/426099
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Jet Model of X‐Ray Flashes, X‐Ray–rich Gamma‐Ray Bursts, and Gamma‐Ray Bursts. I. Power‐Law–shaped Universal and Top‐Hat–shaped Variable Opening Angle Jet Models

Abstract: HETE-2 has provided strong evidence that the properties of X-Ray Flashes (XRFs), X-ray-rich GRBs, and GRBs form a continuum, and therefore that these three kinds of bursts are the same phenomenon. A key feature found by HETE-2 is that the density of bursts is roughly constant per logarithmic interval in burst fluence S E and observed spectral peak energy E obs peak , and in isotropic-equivalent energy E iso and spectral peak energy E peak in the rest frame of the burst. In this paper, we explore a unified jet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(179 citation statements)
references
References 47 publications
13
163
1
2
Order By: Relevance
“…iso relation (Amati relation) discovered in conventional GRBs (Amati et al 2002), which also extends to some previously observed X-ray flash (XRFs) (Lamb et al 2005). Here, E p is the cosmological rest frame spectral peak energy and E iso is the isotropic g-ray energy.…”
Section: Amati Et Al (Submitted) Demonstrated That Grb(xrf) 060218 Wsupporting
confidence: 74%
“…iso relation (Amati relation) discovered in conventional GRBs (Amati et al 2002), which also extends to some previously observed X-ray flash (XRFs) (Lamb et al 2005). Here, E p is the cosmological rest frame spectral peak energy and E iso is the isotropic g-ray energy.…”
Section: Amati Et Al (Submitted) Demonstrated That Grb(xrf) 060218 Wsupporting
confidence: 74%
“…Relative to other Swift detected GRBs, GRB 051117A is rather unremarkable, with a BAT fluence placing it at the mean of the brightness distribution, while its spectral characteristics place it at the soft end of the burst population. In fact based on Lamb's definition (Lamb et al 2005), GRB 051117A qualifies as an X-ray Rich Burst.…”
Section: Grb 051117amentioning
confidence: 99%
“…The number of events detected by SPI-ACS and HETE-2 is relatively low compared to the total number of GRBs detected by HETE-2 during the INTEGRAL mission time. This is not surprising; it is the result of the low sensitivity of SPI-ACS to X-ray flashes and X-ray rich bursts, which constitute approximately 2/3 of the HETE-2 GRB sample (Lamb et al 2005). These events are characterized by an E p <80 keV and thus have their emission maximum below the SPI-ACS energy range.…”
Section: Sample Selectionmentioning
confidence: 99%